The conflict in Ukraine as a threat for the European Union’s integrity - Nychyk, Alina (Wydawnictwo Uniwersytetu Ekonomicznego we Wrocławiu, 2017)
The latest conflict in Ukraine changed the security situation on the European continent significantly and brought into question the adequacy of the present global rule to keep order in the world. The situation in Ukraine showed how key countries could cooperate when protecting human values and democratic standards stated in international agreements. This article presents how the conflict in Ukraine became a threat for the EU’s integrity. It analyses measures implemented by the organization to stop the war in the neighboring country and researches proposals that were rejected during the decision-making procedure. The aim of the work is to examine the ability of the EU to stay cohesive and decisive in the situation of a close external threat. The methods for the research are: qualitative research of secondary data, interviews, scientific analysis and synthesis
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics, 2017, Nr 465, s. 123-129
Keywords: conflict in Ukraine; Russia; EU’s response; sanctions; konflikt na Ukrainie; Rosja; odpowiedź Unii Europejskiej; sankcje